Survival and breeding of Greater Flamingos Phoenicopterus ruber roseus in the wild after a period of care in captivity - Johnson, A R; Green, R E (Wildfowl, 1990)
Of 20-22,000 Greater Flamingos present in southern France in December 1984, 3000 were found dead during a spell of freezing weather in January 1985 and a further 4000 birds are estimated to have died. Of 1000 birds captured in a weakened state during the cold spell and cared for in captivity, 53 adults were marked with plastic rings. About 15% of these birds are estimated to have died shortly after release. Birds that were not seen alive after release tended to have been lighter at release and to have gained less weight during their period in captivity. The subsequent survival and incidence of breeding of birds that were seen alive after release was high.